Uma experiência de inclusão digital na Amazônia: o Programa NavegaPará e o horizonte da democracia representativa. Limites e esperanças - CASTRO, Fábio Fonseca de (Universidade Católica do Rio Grande do Sul, 2022)
The aim of this paper is to discuss the strategy of Digital Inclusion in Amazon. We observe the NavegaPará Program, developed by the Pará government in partnership with Eletronorte, the Federal and municipal governments and civil society organizations. We seek to understand how this program dialogues with a regional development models to create alternatives to the status of “limited development” imposed over the Amazon by the mentality of Brazilian southeast region – political and economical centre of the country. We also seek to understand the political dimension present in the notion of Digital Inclusion.